The Urban Dictionary e o uso da metalinguagem na produção de dicionários virtuais colaborativos - Puppi, Bárbara Branco (2018)
The main objective of this research is to analyze the entries that circulate in The Urban Dictionay (TUD) to investigate if the authors mobilize metalinguistic knowledge when producing the definitions that make up the content of the platform in focus. In order to fulfill this objective we sought theoretical foundation in García (2000) to present the concept of technology that directed the development of the research; we explored aspects related to the making process of dictionaries elaborated by specialists, to distinguish them from virtual dictionaries which are built collaboratively from the knowledge of amateurs. For this it was necessary to explore the ideas of Biderman (1981), Vilela (s / d), Krieger (2006), Bevilacqua and Finatto (2006), Almeida & Gomes (2012) and others; we discussed the concept of grammatization developed by Auroux (1992) and how it applies to research; we sought reference in the studies of Levy (1999) to discuss cyberspace's origin and its relation to the collaborative production of content articulated by Shirky (2008) and to the purpose of this research. In the course of our work, we discovered that cyberspace does not bring with it unprecedented forms of communication and human action, but it allows us to reconfigure practices that were already common among us. One of the practices that the cyberspace gave us was the ability to redesign the production of content process. From the expansion of cyberspace, contents that were previously produced only by professionals specialized in the area of knowledge and in the activity to be performed began to be produced by individuals who, inserted in virtual communities, unite their abilities and interests to produce content and put them into circulation so that they can be accessed by other users who have the same interest. The object of analysis of this research results from this dynamics of content production established by both the birth and diffusion of cyberspace. Since it is constructed from definitions generated by amateurs, TUD allows non-expert users to take ownership of the process of elaborating definitions for the words that are present in the dictionary. In this way, the TUD allowed us to analyze if the users-authors involved in the process of construction of the platform mobilize metalinguistic knowledge when producing the definitions that circulate in the dictionary. However, at the end of the research, we realized that, although the TUD authors-users demonstrate familiarity with the definition genre, there is little mobilization of metallinguistic knowledge, and that the non-involvement of specialized knowledge can compromise the information the authors of TUD provide about the terms circulating on the platform. In addition, it was also possible to see that the tools of collaborative production generated by cyberculture enabled a redesigning movement of the development process of a dictionary.